Development of scratch resistance SiO2 nanocomposite coating for teak wood - Thananthorn Kanokwijitsilp (2018)
Teak wood is widely used for the housing interior and decoration because of its beautiful grains appearance; however, it often suffers from surface damage especially in the tiling application. The remedy is to apply a protective layer such as polyurethane (PU). In this work, the sol-gel inorganic reinforced hard coating formulation based on silicon dioxide (SiO2) nanoparticles (SNPs) and methyltrimethoxysilane (MTMS) was investigated as a protective layer for teak wood. The coating formulation was applied by brushing, followed by pre-cured at 65 °C for 1 hr and cured at 95 °C for 3 hrs, yielding a transparent nanocomposite film. The SiO2 nanocomposite coating showed an improvement in abrasion resistance property, tested with Taber abrasion at 5 N for 1000 cycles, as evidenced by a lower weight loss than an uncoated counterpart. The nanocomposite film also showed a higher wear through resistance than the commercial PU coating. Water can be easily absorbed by uncoated wood while the nanocomposite coated wood showed an improvement in water resistance as evidence by water contact angle. The cross-sectional image showed that the nanocomposite film and the wood surface were forming a physical interlocking. © 2013 IEEE.